Evaluasi kinerja keuangan bank syariah indonesia melalui debt to asset ratio: implikasi terhadap struktur pendanaan dan stbilitas operasional - Sulistyawati, Dewi Indah (Maliki Interdisciplinary Journal, 2025)
The evaluation of Bank Syariah Indonesia’s financial performance through the Debt to Asset Ratio during the 2020–2024 period provides an overview of the bank’s solvency condition and its ability to manage its funding structure. The analysis of the Debt to Asset Ratio is used to examine the extent to which the bank’s assets are financed by liabilities and how this level of leverage reflects its operational stability. Changes in the Debt to Asset Ratio from year to year indicate the dynamics of funding management related to the effectiveness of risk management, asset growth capacity, and the sustainability of the bank’s operations. Through an observation of the movement of the Debt to Asset Ratio over the five-year period, this study provides insights into the relationship between solvency ratios, funding efficiency, and the institution’s resilience to financial pressures. The results of this analysis are expected to offer a holistic perspective on the role of the Debt to Asset Ratio in strengthening the funding foundation and supporting the operational stability of Bank Syariah Indonesia.